Evidence for evolution and selection of drought-resistant genes based on high-throughput resequencing in weedy rice. (18th February 2022) - Han, Bing; Cui, Di; Ma, Xiaoding; Cao, Guilan; Zhang, Hui; Koh, Hee Jong; Han, Longzhi
Abstract : PAPH1 encoding a PAP family protein is identified as a major gene related to drought resistance in weedy rice that has been selected for during de-domestication of cultivated rice. Abstract: Weedy rice ( Oryza sativa f. spontanea ) is a relative of cultivated rice that propagates in paddy fields and has strong drought resistance. In this study, we used 501 rice accessions to reveal the selection mechanism of drought resistance in weedy rice through a combination of selection analysis, genome-wide association studies, gene knockout and overexpression analysis, and Ca 2+ and K + ion flux assays. The results showed that the weedy rice species investigated have gene introgression with cultivated rice, which is consistent with the hypothesis that weedy rice originated from de-domestication of cultivated rice. Regions related to tolerance have particularly diversified during de-domestication and three drought-tolerance genes were identified. Of these, Os01g0800500 was also identified using an assay of the degree of leaf withering under drought, and it was named as PAPH1, encoding a PAP family protein. The drought-resistance capacity of PAPH1 -knockout lines was much lower than that of the wild type, while that of overexpression lines was much higher. Concentrations of Ca 2+ and K + were lower in the knockout lines and higher in the overexpression lines compared with those of the wild type, suggesting that PAPH1 plays important roles in coping with drought stress. Our study therefore provides new insights into the genetic mechanisms underlying adaptive tolerance to drought in wild rice and highlights potential new resistance genes for future breeding programs in cultivated rice.